Pengendalian Hayati Sclerotium rolfsii Sacc. pada Kedelai dengan Binucleate Rhizoctonia - Hardjono Sri Gutomo (Caraka Tani: Journal of Sustainable Agriculture, 2007)
The research was conducted to study binucleate Rhizoctonia as biocontrol agents again Sclerotium rolfsii Sacc. On soybean seedlings in Laboratory and greenhouse. Nine of 57 isolates were identified as binucleate Rhizoctonia. Eight of the nine isolates were non pathogenic and three of them were used in the research as biocontrol agents. The three isolate decreased the disease intensity caused by S. Rolfsii in the greenhouse by 29,17; 14,58 and 41,67%.